Effectiveness measurement: when will we get it right? - Dwyer, Rocky J. (2009)
Credible demonstration of policy or program impacts depends on understanding the distinction between inputs outputs outcomes and indicators. Moreover in order to be trusted public reports on a programs' performance need to focus more selectively on identifying the key measures of performance. In the first place the aim of the article is to provide those involved in the practice of program evaluation with enhanced understanding of the current literature reports and documentation on estimating impacts and results of government programs and policies. Secondly it is designed to share definitions and guidelines used to determine economic impacts. Finally this article includes current best practices involved in measuring incremental impacts all of which we contend enable program evaluation staff providing them with new ways of approaching measurement effectiveness and accountability in a strategic and comprehensive manner.